Compensating for Images of History Produced by ‘Rival’ Historiography: The Case of Czech and Sudeten German Historiographies in 1938–1945 - Pánek, Tomáš (Dějiny – teorie – kritika, 2015)
This contribution is based on a comparative analysis of images of important turning points (symbolic centres) of Czech and Sudeten German history created in 1938–1945 by Czech and Sudeten German historiographies. Its aim is to describe the main strategies these historiographers used to refute or at least compensate the image or interpretation of a historical phenomenon as described by the ‘rival’ historiography. Based on a generalisation, this contribution offers a classification of typical strategies which were used to this purpose. It turns out that on this general level, and although the nationally conditioned content was different, strategies used by the Czech and Sudeten German historiographies were identical. The analysis and generalisation are introduced by a theoretical introduction which offers arguments for the still sadly neglected use of comparative and relational-historical approach to the history of Czech historiography.